High Urinary Sodium Concentrations in Severe SIADH: Case Reports of 2 Patients and Literature Review - Lee, Lynette Mei Yi; Tan, Sarah Ying Tse; Loh, Wann Jia (Frontiers in Medicine, 2022)
We present two cases of severe hyponatremia secondary to syndrome of inappropriate secretion of antidiuretic hormone (SIADH) with very high urine sodium concentrations (>130 mmol/L). The first patient had hyponatremia from traumatic brain injury (TBI) while the second case had a history of recurrent SIADH triggered by various causes including gastritis. In both cases, fluid administration and/or consumption worsened the hyponatremia. Although a low urine sodium of <30 mmol/L is highly suggestive of hypovolemic hyponatremia and good response to saline infusion, there is lack of clarity of the threshold of which high urine sodium concentration can differentiate various causes of natriuresis such as SIADH, renal or cerebral salt wasting. Apart from high urine osmolality (>500 mOsm/kg), studies showed that high urine sodium concentrations (>130 mmol/L) were predictors of poor response to fluid restriction in SIADH. More studies are needed to delineate treatment pathways of patients with very high urine osmolality and urine sodium concentrations in SIADH.